Animal trait ontology: The importance and usefulness of a unified trait vocabulary for animal species - Hughes, L. M. (2008)
Ontologies help to identify and formally define the entities and relationships in specific domains of interest. Bio-ontologies, in particular, play a central role in the annotation, integration, analysis, and interpretation of biological data. Missing from the number of bio-ontologies is one that includes phenotypic trait information found in livestock species. As a result, the Animal Trait Ontology (ATO) project being carried out under the auspices of the USDA-National Animal Genome Research Program is aimed at the development of a standardized trait ontology for farm animals and software tools to assist the research community in collaborative creation, editing, maintenance, and use of such an ontology. The ATO is currently inclusive of cattle, pig, and chicken species, and will include other livestock species in the future. The ATO will eventually be linked to other species (e.g., human, rat, mouse) so that comparative analysis can be efficiently performed between species.